2011
DOI: 10.4103/2229-5119.83955
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic- and antidepressant-like effects of an ethanolic extract of the aerial parts of Hilleria latifolia (Lam.) H. Walt. in mice

Abstract: Background: Anxiety and depression remain the most common psychiatric disorders affecting man. To date, the effi cacy of the drugs for these conditions is very limited and requires the search for newer, bettertolerated, and more effi cacious treatments. The present study evaluated the anxiolytic-and antidepressant-like effects of the ethanolic extract of the aerial parts of Hilleria latifolia (HLE) in murine models. Materials and Methods: The ethanolic extract of the aerial parts of Hilleria latifolia was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…This pentacyclic triterpene has been widely consumed for many centuries without health hazard (Michael et al, 2007; Newman and Cragg, 2007). Studies have shown anxiolytic and antidepressant-like effects of isolated triterpenoids such as α amirin and β amirin (Chen et al, 2005; Rodrigues et al, 2002; Woode et al, 2011). However, being natural products, relative abundance of these triterpenoids varied from species to species.…”
Section: Introductionmentioning
confidence: 99%
“…This pentacyclic triterpene has been widely consumed for many centuries without health hazard (Michael et al, 2007; Newman and Cragg, 2007). Studies have shown anxiolytic and antidepressant-like effects of isolated triterpenoids such as α amirin and β amirin (Chen et al, 2005; Rodrigues et al, 2002; Woode et al, 2011). However, being natural products, relative abundance of these triterpenoids varied from species to species.…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety and depression are the most common psychiatric disorders; already cover 20% of the adult population, suffering from these illnesses at some time during their lives [2][3][4]. It has grown up to be an important area of research interest in psychopharmacology during this decade [5].…”
Section: Introductionmentioning
confidence: 99%
“…Over 20% of the adult population suffers from these illnesses at some time during their lives [1][2][3] . It has become an important area of research interest in psychopharmacology during this decade [4] . Benzodiazepines are among the most prescribed and effective antianxiety drugs used worldwide [5].…”
Section: Introductionmentioning
confidence: 99%